Performance measurement for reverse and closed-loop supply chains - Saibani, Nizaroyani (2010)
Supply chains today continue to have shorter life-cycle products as a result of high rates of innovation. The increasing number of electronic retailing and catalogue sales fulfil the requirement of home shopping. More liberal return policies have been introduced to protect customers' buying rights and at the same time generate more sales. A growing number of environmental regulations are created which involve a wide range of products. All of these circumstances contribute to the reverse flow of products which require manufacturing organisations to strategically manage and deal with the return flows. Reverse supply chains or reverse logistics have attracted the attention of many academics and practitioners and one of the important field studies in this area is of Supply Chain Management. To contribute to the field, this research is purposely carried out to study the performance measurement in reverse supply chains. Reverse logistics networks may be classified into several categories depending on the source of the reverse flow. This research will focus on customer and distribution return flows.